2018
DOI: 10.1096/fj.201801150r
|View full text |Cite
|
Sign up to set email alerts
|

Peroxiredoxin 1/2 protects brain against H2O2‐induced apoptosis after subarachnoid hemorrhage

Abstract: Recent studies suggest that peroxiredoxin1/2 (Prx1/2) may be involved in the pathophysiology of post‐ischemic inflammatory responses in the brain. In this study, we assessed the distribution and function of Prx1/2 in mice after experimental subarachnoid hemorrhage (SAH). We investigated the distribution of Prx1/2 in the brains of mice both in vivo and in vitro using immunofluorescence staining. The expression of Prx1/2 after SAH was determined by Western blot. Adenanthin was used to inhibit Prx1/2 function, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 37 publications
1
37
0
Order By: Relevance
“…Immunofluorescence staining was performed as previously described 11 . Briefly, frozen brain sections (7 μm) and cultured cells on coverslips were fixed in ice-cold acetone and 4% paraformaldehyde, respectively.…”
Section: Immunofluorescence Stainingmentioning
confidence: 99%
“…Immunofluorescence staining was performed as previously described 11 . Briefly, frozen brain sections (7 μm) and cultured cells on coverslips were fixed in ice-cold acetone and 4% paraformaldehyde, respectively.…”
Section: Immunofluorescence Stainingmentioning
confidence: 99%
“…Peroxiredoxins (Prxs) is a superfamily of an ubiquitous cysteine-based anti-oxidant family, and Prxs II is one of the six isoforms of Prx in humans [25]. Prx II contributes to an anti-oxidant effect when it is expressed intracellularly, and has an important function for mediating inflammation when it is expressed extracellularly [26]. Prxs are aberrantly upregulated in several cancers, which has a crucial influence on promoting tumor progression [27].…”
Section: Mir-122mentioning
confidence: 99%
“…Although Prdx1, an RBP (Baltz et al, 2012;Castello et al, 2012;Kim et al, 2012;Kwon et al, 2013;Sebestyén et al, 2016), has been shown to be elevated after ICH (Nakaso et al, 2000), its roles in brain injury after ICH are still largely unknown. Prdx1 is a member of the peroxiredoxin family (Wood et al, 2003) and has been shown to be involved in regulating many pathological processes, such as redox reactions (Yamaguchi et al, 1993), inflammatory responses, apoptosis (Liu et al, 2014(Liu et al, , 2018Min et al, 2018;Lu et al, 2019), and tumorigenesis (Hoshino et al, 2005;Cao et al, 2009). These findings suggest that Prdx1 may also play important roles in regulating the above-mentioned pathological processes to influence the brain injury caused by ICH.…”
Section: Introductionmentioning
confidence: 93%